Adhesion molecules before and after propylthiouracil in patients with subclinical hyperthyroidism - Bilgir,Ferda (2020)
SUMMARY OBJECTIVE This study aimed to investigate the effect of propylthiouracil treatment on adhesion molecules in patients with subclinical hyperthyroidism. METHODS In this study, a total of 168 patients diagnosed with subclinical hyperthyroidism were treated with propylthiouracil for one year. The levels of adhesion molecules, consisting of sICAM-1, sVCAM-1, and sE-Selectin, before and after the treatment were measured and compared. These results were compared with the levels of 148 healthy controls who received a placebo. RESULTS sICAM-1 levels were significantly higher in subclinical hyperthyroidism patients than in healthy controls (*pa=0.000). sICAM-1 levels were significantly decreased after the treatment (**pb=0.000). Despite this decrease in patients with subclinical hyperthyroidism, it did not decrease to the level of the control group. sVCAM-1 did not change before and after propylthiouracil treatment. The level of sE-selectin was similar to that of the pretreatment control group, but it did not have statistical significance, although it increased after the treatment (**pb=0.004). CONCLUSION The sICAM level was significantly higher than the pretreatment values and decreased after the propylthiouracil treatment. However, further studies are needed to reduce the risk of atherosclerosis and cancer in patients with subclinical hyperthyroidism.